The Importance of Economic Education: Preparing Future Generations for Global Economic Challenges - Thi Phuong Thao, Nguyen (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
Economic education has a central role in equipping future generations with a solid understanding of basic economic concepts and the skills needed to face global economic challenges. This abstract summarizes the results of discussions that highlight crucial aspects of economic education, including its role in improving understanding of economic concepts, preparation for global challenges, and development of critical and analytical skills. Discussions also include the linkage of research results to educational policy, a focus on developing ethical attitudes and social responsibility, and how economic education stimulates global collaboration and entrepreneurship. In conclusion, economic education not only provides conceptual knowledge but also forms the attitudes and skills needed to participate actively in the growing global economy.